2019
DOI: 10.1177/1043454219887671
|View full text |Cite
|
Sign up to set email alerts
|

Nurse–Patient Connectedness and Nurses’ Professional Quality of Life: Experiences of Volunteering at a Pediatric Oncology Camp

Abstract: Objective: Pediatric oncology nurses can experience burnout, vicarious traumatization, and compassion fatigue related to the unique stressors of their profession. Opportunities to enhance nurses’ professional commitment and nurse–patient connectedness may mitigate these stressors. This study explored the impact of volunteering at a local oncology camp on pediatric oncology nurses’ professional quality of life and connectedness with their oncology patients. Method and Sample: Pediatric oncology nurses from a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…In the 6-month follow-up interviews, nurses reported that the experience at camp helped them see “kids as kids” when they returned to work in the PICU. The person-factor and patient/family factor categories of the PICU nurses in this study align with the nurse-patient connectedness and professional quality-of-life experiences of pediatric oncology nurses described by Cherven and colleagues 16 …”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In the 6-month follow-up interviews, nurses reported that the experience at camp helped them see “kids as kids” when they returned to work in the PICU. The person-factor and patient/family factor categories of the PICU nurses in this study align with the nurse-patient connectedness and professional quality-of-life experiences of pediatric oncology nurses described by Cherven and colleagues 16 …”
Section: Discussionsupporting
confidence: 77%
“…The person-factor and patient/ family factor categories of the PICU nurses in this study align with the nurse-patient connectedness and professional quality-of-life experiences of pediatric oncology nurses described by Cherven and colleagues. 16 The 3rd category, work-related factors, revealed that the camp experience had a positive impact on the nurses' perception of their work in the PICU. In the 6-month postcamp interviews, nurses described improved relationships among nurse colleagues, which may mitigate the signs and symptoms of burnout related to compassion fatigue and moral distress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of adequate education and psychosocial support, specialized highstress work environments can result in the development of ineffective coping strategies that further increase a clinician's risk (Sabo, 2008;Sekol & Kim, 2014). Specific stressors found in subspecialty settings such as inpatient and outpatient pediatric hematology, oncology, apheresis, and stem-cell and bone marrow transplant units lend themselves to the nurse experiencing vicarious traumatization (Sekol & Kim, 2014), compassion fatigue (Boyle & Bush, 2018;Hecktman, 2012), ethical conflict (Bartholdson et al, 2015;Weiner et al, 2021), moral distress (MD; Dyo et al, 2016;Weiner et al, 2021), grief (Conte, 2014;Montgomery et al, 2017), burnout (De la Fuente-Solana et al, 2021;Hecktman, 2012;Sekol & Kim, 2014;Spinetta et al, 2000), and job dissatisfaction due to feelings of helplessness (Cherven et al, 2020;De la Fuente-Solana et al, 2021;Sekol & Kim, 2014). Consequently, nurses may begin to withdraw emotionally and physically from their work (Boyle & Bush, 2018) resulting in reduced quality of care (Salmond et al, 2019), increased patient safety incidents (Dunn et al, 2021;Garcia et al, 2019), increased absenteeism (Salmond et al, 2019;Spinetta et al, 2000), and poor staff retention (Buckley et al, 2020;Mahon, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, low professional quality of life of nurses can have a negative impact on patient care and quality of life. Findings show that nurses working in various fields experience negative stressors that impact their professional quality of life (Cherven et al, 2020;Duarte et al, 2016;Kwak et al, 2020). Good working conditions that provide safety for employees can enhance their emotions and help them to improve their mental and physical health at the workplace and thus increase their sense of competence and job satisfaction.…”
Section: Discussionmentioning
confidence: 99%